AKTIVITAS PERDAGANGAN SAHAM SEBELUM DAN SESUDAH PERUSAHAAN MELAKUKAN PEMECAHAN SAHAM DAN PENGGABUNGAN SAHAM DI BURSA EFEK INDONESIA TAHUN 2014-2016 (Studi Komparatif Pada Harga, Likuiditas, Volume dan Frekuensi Perdagangan Saham) - Mohammad Jusuf Supriadi; Amirul Fathoni; Very Andrianingsih (Fakultas Ekonomi dan Bisnis, 2018)
This research uses 11 day observation method 5 days before stock split / reversesplit, 1 day as observation method, and 5 days after stock split / reverse split event. Dataanalysis method used is paired sample different test. After testing the normality there are2 tests that is different test method wilcoxon signed rank test to test stock trading activityon companies doing stock split action and test method different paired sample t-test totest stock trading activity in company doing reverse split. showed no price difference,liquidity, volume and frequency of shares for companies doing reverse split action. Thisshows that stock split action does have a positive signal to attract investors, while StockLikuidity (stock split) and reverse split action are not.